Application of Aswaja Character in Religious Programs Through the Approach of B.F. Skinner with Reinforcement Model at Islamic Elementary School Nurul Bayan Sumenep - Noor Alfi Fajriyani; Maemonah Maemonah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Aswaja character education is important to instill in learners at a young age. Because with the cultivation of aswaja character education in students, it will form a character in accordance with the character of Islamic norms, and in harmony with the nation’s noble values. This research uses descriptive qualitative approach methods. The goal of this reseacrh was to see how the type of application of